The Gini Concentration Ratio and the Minor Concentration Ratio: A Two Parameter Index of Inequality - Hagerbaumer, James B. (The Review of Economics and Statistics, 1977)
James B. Hagerbaumer, The Gini Concentration Ratio and the Minor Concentration Ratio: A Two Parameter Index of Inequality, The Review of Economics and Statistics, Vol. 59, No. 3 (Aug., 1977), pp. 377-379